2000
DOI: 10.1006/exnr.2000.7408
|View full text |Cite
|
Sign up to set email alerts
|

Convection-Enhanced Delivery of AAV Vector in Parkinsonian Monkeys; In Vivo Detection of Gene Expression and Restoration of Dopaminergic Function Using Pro-drug Approach

Abstract: Using an approach that combines gene therapy with aromatic L-amino acid decarboxylase (AADC) gene and a pro-drug (L-dopa), dopamine, the neurotransmitter involved in Parkinson's disease, can be synthesized and regulated. Striatal neurons infected with the AADC gene by an adeno-associated viral vector can convert peripheral L-dopa to dopamine and may therefore provide a buffer for unmetabolized L-dopa. This approach to treating Parkinson's disease may reduce the need for L-dopa/carbidopa, thus providing a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
236
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 384 publications
(249 citation statements)
references
References 33 publications
10
236
1
Order By: Relevance
“…This is also supported by a dose-response study that showed loss of axonal transport with decreasing titers of AAV vectors (Kaspar et al, 2003). Alternatively, widespread AAV distribution may be achieved with pressure-mediated, convection-enhanced delivery (Bankiewicz et al, 2000;Nguyen et al, 2001). Coinjection of AAV with hyperosmotic agents or molecules that bind to their receptors may also provide broader distribution (Mastakov et Comparison of TPP1 activity in AAV2 CU hCLN2-or AAV5 CU hCLN2-treated brains at 13 weeks after injection.…”
Section: Discussionmentioning
confidence: 87%
“…This is also supported by a dose-response study that showed loss of axonal transport with decreasing titers of AAV vectors (Kaspar et al, 2003). Alternatively, widespread AAV distribution may be achieved with pressure-mediated, convection-enhanced delivery (Bankiewicz et al, 2000;Nguyen et al, 2001). Coinjection of AAV with hyperosmotic agents or molecules that bind to their receptors may also provide broader distribution (Mastakov et Comparison of TPP1 activity in AAV2 CU hCLN2-or AAV5 CU hCLN2-treated brains at 13 weeks after injection.…”
Section: Discussionmentioning
confidence: 87%
“…14 Previous studies, including our own, have demonstrated that AAV vector-mediated delivery of dopamine-synthesizing enzymes results in efficient long-term expression of the transgene in the striatum. [14][15][16] The present study used the Sauer and Oertel partial PD model. 17 In this model, intrastriatal injection of 6-OHDA induces progressive retrograde degeneration of DA neurons that starts between 1 to 2 weeks after lesioning and continues over 8 to 16 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In one vector formulation that included an excess of empty AAV capsids produced by a column purification method, we observed reduction of AADC distribution associated with highly focal AADC expression determined by postmortem histochemical examination (Eberling et al, 2003). Diffuse expression of AADC is ordinarily generated by convection-enhanced delivery (CED) of CsCl-purified vector (Bankiewicz et al, 2000). The association of the appearance of severe LID with focal delivery of AADC has led to the insight that highly focal delivery of AADC activity could be used to as a research tool to probe the neural mechanisms underlying dyskinesias.…”
Section: Introductionmentioning
confidence: 99%
“…Transduced with this vector, striatal neurons gain the ability to produce DA from exogenous L-dopa, a dopamine precursor. Briefly, expression of AADC in the striatum of parkinsonian rodents and monkeys greatly enhanced the efficacy of exogenously supplied L-dopa (Bankiewicz et al, 2000;Sanchez-Pernaute et al, 2001). In PD, it is primarily the loss of L-dopa conversion efficiency that underlies the progressive wearing off of L-dopa responsiveness.…”
Section: Introductionmentioning
confidence: 99%